2019
DOI: 10.1186/s42269-019-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and chemical evaluation of dried pomegranate (Punica granatum L.) peels and studying the impact of level of inclusion in ration formulation on productive performance of growing Ossimi lambs

Abstract: Background: By 2050, the world will need to feed an additional 2 billion people and require 70% more meat and milk. The increasing future demand for livestock products, driven by increases in income, population, and urbanization will impose a huge demand on feed resources. A huge quantity of fruit and vegetable wastes and byproducts from the fruit and vegetable processing industry are available throughout the world that encourages to using it as a new source feeds in animal ration formulation. Methods: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Data of Table (3) that illustrated the vitamin contents of DPP cleared that it contained 15.12, 5.02, 0.496, 0.395 and 0.131 mg/100 g for vitamin C , vitamin E, vitamin A , vitamin B1, vitamin B2 , respectively. The result values were in agreement with those established by (Rowayshed et al, 2013 andOmer et al, 2019). The presence of vitamins naturally in DPP is one of the most important factors that make DPP have an antioxidant, antimicrobial, and chemo preventive cancer properties.…”
Section: Vitamins Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…Data of Table (3) that illustrated the vitamin contents of DPP cleared that it contained 15.12, 5.02, 0.496, 0.395 and 0.131 mg/100 g for vitamin C , vitamin E, vitamin A , vitamin B1, vitamin B2 , respectively. The result values were in agreement with those established by (Rowayshed et al, 2013 andOmer et al, 2019). The presence of vitamins naturally in DPP is one of the most important factors that make DPP have an antioxidant, antimicrobial, and chemo preventive cancer properties.…”
Section: Vitamins Contentsupporting
confidence: 92%
“…So, it could be mentioned that DPP considered a major source of vitamins. These results demonstrated that DPB was a good source of nutritious macro and micro minerals (Omer et al, 2019).…”
Section: Vitamins Contentmentioning
confidence: 73%
See 1 more Smart Citation
“…However, result of the current study is in disagreement with Kotsampasi et al (2014) who stated that the addition of PP to the total mixed ratio (TMR) at concentrations of 0, 120, and 240 g kg -1 did not significantly affect live weight, live weight gain, DM consumption, and feed utilization. Omer et al (2019) who stated in their study that dried pomegranate peel can be used safely in sheep feeding at level of 1% because this level realized the best growth performance and depressed the price of ration cost and recorded the best relative economic efficiency (Omer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The biologically active ingredients are present in the peel, seeds, and arils of the pomegranate. The pomegranate peel, consisting of 26-30% of the total weight of fruit [2], is considered the main medicinal part and contains different minerals, essential amino acids, sugars, unsaturated and saturated fatty acids, tocopherols, sterols, terpenoids, and high concentrations of polyphenols (anthocyanins, flavonoids, ellagitannins, and alkaloids) [1,3,4]. Ellagitannins, the primary polyphenols of pomegranate, consist dominantly of punicalagin, punicalin, ellagic acid, and gallic acid.…”
Section: Introductionmentioning
confidence: 99%